The immunoglobulin superfamily ligand B7H6 subjects T cell responses to NK cell surveillance - Kilian, Michael; Friedrich, Mirco; Lu, Kevin Hai-Ning; Vonhören, David; Jansky, Selina; Michel, Julius; Keib, Anna; Stange, Saskia; Hackert, Nicolaj; Kehl, Niklas; Hahn, Markus; Habel, Antje; et al. (Science immunology, 2024)
Understanding the mechanisms that regulate T cell immunity is critical for the development of effective therapies for diseases associated with T cell dysfunction, including autoimmune diseases, chronic infections, and cancer. Co-inhibitory “checkpoint molecules,” such as programmed cell death protein-1, balance excessive or prolonged immune activation by T cell-intrinsic signaling. Here, by screening for mediators of natural killer (NK) cell recognition on T cells, we identified the immunoglobulin superfamily ligand B7H6 to be highly expressed by activated T cells, including patient-infused CD19-targeting chimeric antigen receptor (CAR) T cells. Unlike other checkpoint molecules, B7H6 mediated NKp30-dependent recognition and subsequent cytolysis of activated T cells by NK cells. B7H6+ T cells were prevalent in the tissue and blood of several diseases, and their abundance in tumor tissue positively correlated with clinical response in a cohort of patients with immune checkpoint inhibitor-treated esophageal cancer. In humanized mouse models, NK cell surveillance via B7H6 limited the persistence and antitumor activity of CAR T cells, and its genetic deletion enhanced T cell proliferation and persistence. Together, we provide evidence of B7H6 protein expression by activated T cells and suggest the B7H6-NKp30 axis as a therapeutically actionable NK cell-dependent immune checkpoint that regulates human T cell function.